2011
DOI: 10.1007/978-3-642-19811-3_26
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Software Updates: Should You Build a Dynamic Updating Infrastructure?

Abstract: Abstract. The ability to adapt software systems to fix bugs, add/change features without restarting is becoming important for many domains including but not limited to finance, social networking, control systems, etc. Fortunately, many ideas have begun to emerge under the umbrella term "dyanamic updating" to solve this problem. Dynamic updating is critical to address certain software evolution needs. Dynamic updating literature evaluates such systems in terms of coverage (i.e. what type of code changes are sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
4
Order By: Relevance
“…Moreover, number of authors have demonstrated other 15 evaluation metrics including availability metrics [6, 37 ], memory usage [41, 136 ], number of violations [77, 81 ], memory footprint [22, 77 ], energy cost [54, 106 ], update cost [63 ], clock cycles for DSU model [93 ], duration of time‐division multiplexing slot in multiprocessor [133 ], measuring the impact changes on resource demands [41 ], patch size [14 ], number of errors [90 ], success‐rate [35 ], simulation of two threads to measure the number of accepted and/or rejected update requests in different workloads [134 ], run the old version in a standard JVM (Java Virtual Machine) to record some performance metric as a baseline [87 ], and before/during/after the update measures [65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, number of authors have demonstrated other 15 evaluation metrics including availability metrics [6, 37 ], memory usage [41, 136 ], number of violations [77, 81 ], memory footprint [22, 77 ], energy cost [54, 106 ], update cost [63 ], clock cycles for DSU model [93 ], duration of time‐division multiplexing slot in multiprocessor [133 ], measuring the impact changes on resource demands [41 ], patch size [14 ], number of errors [90 ], success‐rate [35 ], simulation of two threads to measure the number of accepted and/or rejected update requests in different workloads [134 ], run the old version in a standard JVM (Java Virtual Machine) to record some performance metric as a baseline [87 ], and before/during/after the update measures [65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Para mensurar o potencial benefício do uso do mecanismo utilizamos o modelo de avaliação quantitativo proposto em [5], que leva em consideração a sobrecarga de processamento do mecanismo, os benefícios das atualizações e o tempo que o serviço fica indisponível no caso da atualização estática.…”
Section: Objetivo E Abordagemunclassified
“…Detalhando a arquitetura do sistema de componentes SCS e os primeiros esforços de atualização dinâmica implementados para ele; o capítulo 3 descreve o mecanismo de atualização dinâmica implementado para permitir a aplicação das atualizações propostas; o capítulo 4 se aprofunda nos detalhes do estudo do OpenBus, os principais tipos de atualizações e as versões utilizadas para a atualização; o capítulo 5 apresenta os experimentos feitos com o mecanismo para demonstrar sua expressividade, medir a sobrecarga de processamento e utiliza um modelo de avaliação quantitativo [5] para validar o uso da atualização dinâmica no sistema estudado; o capítulo 6 apresenta os trabalhos relacionados de atualização dinâmica e faz uma avaliação comparativa do mecanismo implementado com as abordagens apresentadas nos trabalhos relacionados, utilizando o arcabouço de avaliação gerado a partir do OpenBus; por fim, o capítulo 7 apresenta o resumo da avaliação, as considerações finais, consolida as contribuições e sugere alguns trabalhos futuros que darão continuidade ao estudo.…”
Section: Estrutura Do Documentounclassified
See 2 more Smart Citations